Strategi Promosi Urban Casual Di Media Sosial Instagram - Aulia Pebriani Amarudin; Risna Nurfazriyanti; Tiara Mediana; Yuliani Sadida (Cebong Journal, 2021)
The purpose of this study was to determine the effect of promotion through social media on interest in buying Instagram fashion on Urban Casual account followers. The type of research that we use in this research is descriptive qualitative research. In detail, qualitative provides space for researchers to explore descriptively about the phenomenon under study, in order to obtain a policy to take action or attitude. The population in this study were all followers on the Urban Casual Instagram account. The types and sources of data in this study were collected based on the grouping of primary data and secondary data. Primary data was obtained through interviews with the owner of the urban casual, namely Muhamad Ridho Amarudin, as well as through field observations. Secondary data is data obtained from existing journals and documents, while the data collection technique is through triangulation collection techniques. Analysis of the test data used is a narrative analysis technique, where this narrative analysis focuses more on how the marketing strategy plan is carried out by the owner of Urban Casual. The conclusion in this study is that there is a significant positive effect between promotion through Instagram social media on fashion buying interest on Urban casual account followers. This is evidenced from the results of the sales table in 2019 to 2021.